Ev tipi buzdolaplarında buz yapma süresinin deneysel ve teorik incelenmesi - Şimşek, Sevda (Fen Bilimleri Enstitüsü, 2016)
Geçmişe bakıldığında firmalar tüketicinin birincil ihtiyaçları kabul edilen yiyecek saklama, çamaşır yıkama gibi ihtiyaçlarını karşılamayı amaçlamışlardır. Günümüzde ise bu tarz arayışlar hala geçerlidir fakat yenilikçi buluşların yanı sıra firmalar tüketici hayatında kolaylık sağlayacak çalışmalara da önem vermektedir ve bu yönde faaliyetlerini günden güne arttırmaktadır. Artan bu faaliyetler içerisinde beyaz eşya sektörünün payı oldukça büyüktür. Beyaz eşya sektöründe ise buzdolabı bu anlamda temel atılımlar yapmaktadır. Buzdolabında tüketici konforunu arttırmak için yapılan çalışmalardan biri, özellikle yaz aylarında fazlaca kullanılan buzun yapım süresinin kısaltılmasıdır. Tüketici dolapta mevcut bulunan buzu kullandıktan sonra yeniden buz oluşturmak için geçen sürenin fazla olduğunu ve kısaltılması gerektiğini talep ettiği için firmalarda bu alandaki çalışmalarını yoğunlaştırmıştır. Tez kapsamında da; ev tipi buzdolaplarında taze gıda saklama bölmelerinde yer alan buz yapma ünitesinde şebeke suyu kullanılarak buz tepsisine beslenen suyun buz haline gelmesi için geçen sürenin kısaltılması için deneysel ve teorik olarak çalışmalar yapılmıştır. Bu süreçte öncelikle mevcut durum incelenmiştir. Buz yapma ünitesinin iç yapısı incelendiğinde bir adet buharlaştırıcı, buharlaştırıcıdan gelen soğuk havayı ünite içerisine üfleyen fan, fanın belli mesafe uzağında konumlandırılmış on hücreli buz tepsisi bulunmaktadır. Yapılan CFD çalışmalarında fan tarafından gönderilen havanın yoğun olarak buz tepsisinin alt yüzeyine temas ederek buz tepsisinin üst kısmına geçiş yaptığı ve emiş kanalı boyunca ilerleyerek buharlaştırıcı tarafından tekrar emildiğini göstermektedir. Literatür ve patent araştırması buz yapma ünitesinin iç yapısı ve zorlanmış taşınım durumu göz önüne alınarak yapılmıştır. Literatür ve patent araştırması yapılırken eş zamanlı momentum ve enerji denklemleri boyutsuzlaştırarak, elde edilen belirsiz sayıları nelerin etkilediği tespit edilmiş ve böylelikle deney düzeneğinde incelenecek parametreler belirlenmiştir. Sonuç olarak hava debisi, buz kabı üzerine fan tarafından üflenen hava sıcaklığı, buz kabına şebekeden beslenen su miktarı ve yoğuşma sıcaklığı olmak üzere dört adet parametre belirlenmiştir. Bu parametreler Minitab programında girildiğinde otuz dört adet deneyden oluşan deney çizelgesi oluşturulmuştur. Oluşturulan deney çizelgesi iki operatör eşliğinde gerçekleştirilmiştir. Deney sonuçlarının Minitab da analizi sonucunda deney çıktısı olarak belirlenen süreyi etkileyen parametreler ve yüzdelik oranları belirlenmiştir. Sonraki adımda deney kurgusu teorik açıdan incelenmiştir. Fan ile buz tepsisi üzerine beslenen hava akışı tarafından birim zamanda buz tepsisinde bulunan sudan çekilen ısı miktarının, buz tepsisinde bulunan suyu buz haline getirmek için gerekli enerji miktarına oranlanması sonucunda süre hakkında gerekli teorik yaklaşım elde edilmiştir. Bu süreçte hal değiştirme sırasında buz oluşumunun zamana bağlı olarak değiştiği dikkate alınmış ve bu kısım için teorik irdeleme iterasyon yapılarak, kümülatif bir şekilde yapılmıştır. Teorik kısımda elde dilen veriler deneysel kısımdan elde edilen veriler ile kıyaslanmış ve aralarındaki fark %7,5 olarak belirlenmiştir. Tez çalışmasının son bölümünde yapılan deneysel çalışmalardan elde edilen sonuçlar ile teorik olarak incelemeler karşılıklı değerlendirilerek buz yapma süresini etkileyen temel faktörler belirlenmiş ve bu alanda ileride yapılacak çalışmalar için öneriler sunulmuştur.

At past time, the big companies aim to supply the primary needs of the consumers such as food storage, washing. But now, there are like this aims of company however this company that have innovations attaches great importance to this work which provide ease for life of consumer and their activities in this direction increases day by day. Increasing the share of white goods sector in these activities is quite large and the refrigerator is making fundamental strides in the white goods sector in this regard. One of the studies in order to increase consumer comfort in the refrigerator is decreasing period of making ice. Especially in the summer, after consumer use present ice in refrigerator, they have to wait long period for new making ice. They think this period, which is making new ice cubs, is so long and so they claimed that this period should be shortened. For this request, companies intensify their studies at this area. In this study; experimental and theoretical investigation for shorten making ice period at household refrigerator is made. This experiment is made at the ice-making unit which is at fresh-food storage compartment and building water reservoir is used to supply water on the ice-making tray. Primarily, the present situation is examined. There are finned evaporators which supply cold air cycle; a fan which blown cold air coming from evaporator into the ice-making unit, ice-making tray with ten cells which is positioned at a certain distance away from the fan. Cold air from the evaporator is absorbed by fan and this air which heats a few degree at this distance is blown into the ice-making unit. Firstly, this air indicates laminar flow characteristics since it hit the ice-making tray. After it passes this tray, it comes back evaporator during suction channel. To be able to effectively use this air is important. On the other hand the important is where the air intensified. For this reason, Comutational Fluid Dynamics (CFD) program was used. Thanks to this analysis, it has been identified where flow is concentrated at under the ice-making tray. Before any improvement, literature and patent searches were made. At patent searches, the following processes were seen. With plane bottom of the ice-making tray, flow direction is canalized on the tray in order to use more effective cold air, There are one more for canalizing flow on the tray, cold air redirect the bottom of the tray by notch in the tray, Improvement for location of evaporator have been done, hereby, ice-making tray is in close contact with evaporator, Water which is used for making ice cubs is cooled at a small reservoir which is positioned next to the ice-making tray. While there are much patent for this topic, number of literature is not much. Generally topic of literature research is freezing events are found in nature. Literature research is being performed at the same time indefinite numbers are obtained by using the momentum and energy equations. At this manner, experimental parameters was obtained. They are; blown air temperature, airflow, the amount of water, condensing temperature Using these parameters, experiment schedule has been generated by Minitab program and thirty-four experiments has been obtained with four parameters, two repeat, two main value and full factorial. Two operators made this experiment at experiment schedule. At this time, most important thing is that this experiment is done in the same way to avoid large differences between the results. For each condition, experiments are performed and results of these experiments were analyzed by Minitab. End of this analysis, It is determined which parameters are effective for time which is output. They are; Blown air temperature; Increase air temperature which blown on the ice-making tray by fan at primarly time had a negative impact on time of ice-making because of that it caused increasing difference between water temperature and air temperature, Airflow; Increase the airflow when the airflow is analyzed, it means the amount of the cold air which instant passing through the unit area increase. Therefore, the volume of water in the ice tray when the contact is applied more by the cold weather. This situation reduces the formation of ice time. The amount of water; Amount of water means the amount of heat, which is drawn from water, is increased by cold air, which fan blown into unit. Because of this reason, the more amount of water is, the more time of ice making is. Condensing temperature; Increase or decrease in the specified temperature range of the condensing temperature did not affect the duration of the ice occurred. This effective parameters was analyzed on Minitab and was showed effects of this parameters on pie chart. It is easly seen that on pie chart, the greatest impact is air flow and percentiles of air flow is 37,8% and second important impact is amount of water and its percentiles is 34,9%, and final effective paremeter is blown air temperature and its percentiles is 17,7%. Effect of condensing temperature can be neglect. Reason of this neglect is that tolerance is 0,005 on industrial area. İf P-value is bigger than 0,005, this parameter can be neglect. The remaining share on pie chart can include dual or triple effect of parameters, moisture induced impact or vibration induced impact. Finally on the experimental period, uncertainty analysis was calculated. Uncertainty analysis is calculated for terms of the measurement. In this study, there are two parameters which were measured. They are velocity and temperature. Velocity is used to find Reynolds number which is used to Nusselt number. And all of them are used to find heat transfer coefficient. Because of this, uncertainty analysis should calculate for heat transfer coefficient. Uncertainty analysis was found ±0,26 [W/m^2K] with using method of Kline and McClintock . Other term is temperature. The temperature measurements were taken from many areas and this values of temperature are used to determine period of ice making. For this reason, uncertainty analysis of time was calculated with using Minitab and this value is ±5,4 [dk]. After the experimental period, theoretical study is made. This study was made under two headings. They are; Theoretical investigation of thermal quantity taken from water on unit time by the Air Flow Theoretical investigation of required energy quantity for in a certain amount of water which will make ice At first part of theoretical study, firstly type of air flow is determined. There are the heat exchange between fixed plane and moving air. Because of this type exchange, convection heat-exchanger is used. Into ice-making unit air flow is done by fan and so it is called forced convection. The amount of heat transfer is calculated by multiplying the temperature difference and thermal resistance. There are two direction air flows that are under ice-making tray and coming back air on ice-making tray. Because of this reason, ice that will be in cells on tray is occurred from outside to inside with thin layer. This every thin layer occur resistance for next thin layer. And there are five thermal resistances. On ice-making tray, there are two thermal resistances; Between fixed water on tray and moving air, there are heat transfer by convection Between ıce layer and , there are heat transfer by conduction, Under ice-making tray, there are three thermal resistances; Between under fixed ice-making tray and moving air, there are heat transfer by convection, On ice-making tray, there is heat transfer by conduction, Between ice layers, there is heat transfer by conduction. At second part of theoretical study, changes in state diagram are used and there are three equations for heat exchange. Calculation of required energy for water which has room temperature drop state changing temperature, Calculation of required energy for during state changing temperature, Calculation of required energy for water on state changing temperature to -10C The above calculations are done with Microsoft Excel 2010. This calculation is done time-dependent because of ice layer resistance. When theoretical solutions compared with experimental solutions, there are almost 7,5% difference. At final part of this thesis, main parameters are determined with solutions of experimental and theoretical. And proposals have been made for next studies.
Experimental and theoretical investigation of the period to ice in household refrigerators
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Keywords: Soğutma ve soğutma makineleri; Tasarım ve yapım; Buharlaştırıcılar; Soğutucular; Refrigeration and refrigerating machinery; Design and construction; Evaporators; Refrigerators